KERAGAMAN SERTA DISTRIBUSI LOBSTER ANGGOTA PALINURIDAE DAN SCYLLARIDAE DI PERAIRAN PANTAI PULAU LOMBOK - , LALU ACHMAD TAN TILAR WANGSAJATI SUKMARING KALIH; , Drs. Trijoko, M.Si. ([Yogyakarta] : Universitas Gadjah Mada, 2013)
because it is known to contain nutrients and high commercial value. Two arrested common lobster family is Palinuridae and Scyllaridae. Many family members lobster is unknown nature, characteristics, distribution and its potential. Lombok Island becomes center of a growing maintenance lobster in Indonesia because it has a broad rocky coastal waters. Scientific study of lobster species diversity in the area is still measly. This research aims to determine the diversity, phenetic species relationships and distribution of Palinurid and Scyllarid lobster in Lombok Island coastal waters. Sampling was conducted on seven points, in the Grupuk Bay & Srenting, Sepi Bay, Labuan Poh & Pelangan, Akar-akar & Sukadana, Gili Indah, Sugian Strait and Tlong-elong. This research was conducted for 4 months, from March to July 2012. Samples that have been caught were identified using âFAO Species Catalogue Vol. 13 Marine Lobster Of The Worldâ. Distribution of each species is presented in the distribution maps. Identification results showed that there are 6 species of lobster, each belonging to the Palinurid and Scyllarid lobster. Palinurid members identified as Panulirus homarus, P. penicillatus, P. longipes, P.versicolor and P. ornatus. Scyllarid members were identified as Parribacus antarticus. Palinurid lobster have a wider distribution of the species especially Panulirus versicolor. Station 1 (Grupuk Bay & Srenting) with 4 species and Station 2 (Sepi Bay) with 5 species is an area that has the highest diversity of lobster.